Cortisol levels versus self-report stress measures during pregnancy as predictors of adverse infant outcomes: a systematic review. (2nd January 2022) - Caparros-Gonzalez, Rafael A.; Lynn, Fiona; Alderdice, Fiona; Peralta-Ramirez, Maria Isabel
Abstract: Systematically review existing evidence to (1) identify the association between self-report stress and cortisol levels measured during pregnancy; and, (2) assess their association with adverse infant outcomes to determine which is the better predictor. A systematic review was conducted in accordance with PRISMA guidelines. Search terms focused on pregnancy, psychological stress and cortisol. Nine electronic databases were searched, in addition to reference lists of relevant papers. Eligibility criteria consisted of studies that included measurement of self-reported psychological stress, cortisol and assessed their associations with any infant-related outcome. Further limits included studies published in English or Spanish with human female participants. A meta-regression was not feasible due to differences in study samples, measurement tools employed, types of cortisol assessed and outcomes reported. A narrative synthesis was provided. 28 studies were eligible for inclusion. Convergent validity between self-report measures and cortisol was reported by three studies (range r  = 0.12–0.41). Higher levels of self-report stress were significantly associated with intrauterine growth restriction (fetal biparietal diameter, low fetal head circumference, abdominal circumference), low gestational age at birth, low anthropometric measures (birth length, head circumference, length of the neonate), poor infant neurodevelopment (cognitive development) and potentially pathogenic gut microbiota (Clostridiaceae Clostridium, Haemophilus) in six studies. Higher cortisol levels were significantly associated with intrauterine growth restriction (fetal biparietal diameter, low fetal head circumference, abdominal circumference), low gestational age at birth, low infant birth weight, poor infant neurodevelopment (attention scores on the Network Neurobehavioral Scale) and low levels of potentially protective gut microbiota (Lactobacillus, Slackia and Actinobaculum) in 13 studies. Of the studies that assessed which type of measure was a better predictor of infant outcomes ( n  = 6), there was agreement that cortisol levels were statistically better at predicting adverse outcomes than self-reported stress. Self-report stress measures appear to be modest predictors of adverse infant outcomes in comparison to cortisol. A number of methodological limitations need to be addressed in future studies to help understand the relationship between cortisol and self-reported stress and how they are related to adverse infant outcomes.